PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH PERTAMA - Hamrina, Hamrina; Jahidin, Jahidin; Bakareng, Sitti Wirdhana (-)
ABSTRACT            The aims of this research are to know the difference of creative thinking skill between students who learn using problem-based learning model with scientific approach, to know the difference of students’ learning motivation between who learn using problem-based learning model with scientific approach and to know the efficacy of learning motivation to creative thinking skill. The research design is post-test only control group, used 123 students as sample, then divided into 63 students as experimental group and 60 students as control group. The results showed that creative thinking skill in experimental group had maximum score of 93.75, minimum score of 62.5, average score of 77.98, deviation standard score of 6.91, while control group had maximum, minimum, average and deviation standard score of 81.25, 50, 67.09 and 7.36, respectively. Meanwhile, learning motivation of experimental group obtained a maximum score of 90.67, minimum score of 61.33, average score of 76.77 and a standard deviation of 6.97, the control group obtained a maximum, minimum, average and deviation standard score of 89.33, 44.00, 60.89 and 8.35, respectively. The result of t test shows the creative thinking skill and learning motivation, both experimental and control group, gain a probability value of 0.00 with 5% confidence level. The effect size of learning motivation on creative thinking skill is obtained by the value of β in experimental group of 0.958 (95.8%) and in control group of 0.907 or 90.7%. Effect size of proble-based learning model is higher about 5% than scientific approach learning.Keywords: Learning Model, Problem Based Learning, Scientific Method, Creative Thinking, Motivation, Junior High School Students